The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.21608/ajdsm.2020.25745.1031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Simvastatin and Antioxidant mix on pulpotomized young permanent teeth: A clinical and radiographic study

Abstract: Objective: The objective of this study was to evaluate, clinically and radiographically, the effect of Simvastatin and Antioxidant mix on pulpotomized young permanent teeth. Subjects & Methods: Pulpotomy was performed in 54 vital decayed young permanent molars that were indicated for vital pulp therapy. The molars were classified randomly into three equal groups: Group A: molars receiving Simvastatin after pulpotomy (n=18); Group B: molars receiving Antioxidant mix after pulpotomy (n=18); Group C: molars were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…In their study of the effectiveness of 3Mixtatin (Simvastatin + 3Mix antibiotic) as a new pulp capping biomaterial in DPC of human primary molars, Aminabadi et al (34) concluded that the radiographic and clinical results of the 3 Mixtatin group showed it to be a good alternative for DPC of primary molar teeth. Moreover, Abd Elmegeid et al (35) concluded that Simvastatin and Antioxidant mix pulpotomy are more cost-effective, handled easily, and biocompatible. It has been shown to have the potential to be an excellent pulpotomy agent when treating young, important permanent teeth.…”
Section: Success Ratementioning
confidence: 99%
“…In their study of the effectiveness of 3Mixtatin (Simvastatin + 3Mix antibiotic) as a new pulp capping biomaterial in DPC of human primary molars, Aminabadi et al (34) concluded that the radiographic and clinical results of the 3 Mixtatin group showed it to be a good alternative for DPC of primary molar teeth. Moreover, Abd Elmegeid et al (35) concluded that Simvastatin and Antioxidant mix pulpotomy are more cost-effective, handled easily, and biocompatible. It has been shown to have the potential to be an excellent pulpotomy agent when treating young, important permanent teeth.…”
Section: Success Ratementioning
confidence: 99%
“…Statin, a hyperlipidaemic drug (3-hydroxy-3-methylglutaryl-coenzyme A). Since they have been used for so long and are the first line of treatment for hyperlipidemia, they are known to be economical and safe [1]. The statins are safe and efficient therapeutics for lowering liver cholesterol production and the production of low-density lipoprotein (LDL) cholesterol, also called bad cholesterol, which is associated with the development of cardiovascular diseases and stroke [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%